First rewrite the formula by moving all the terms to the left side:
-x^2 + 4x - 3 = 0
A) Find the discriminant using the formula b^2 -4(ac)
where a is the term in front of x^2, which is -1 ( -x is can also be written as -1x)
b = 4 and c = 3
Now you have 4^2 - 4(-1-3) = 16 - 12 = 4
The discriminant is 4.
Because the discriminant is greater than 0, there are 2 real roots.
B) -x^2 + 4x - 3 = 0
Using the quadratic formula -b+/- SQRT(b^2-4(ac) / 2a
Replace the letters with their values like in Part A:
-4 +/- SQRT(4^2-4*(-1*-3) = 2 * -1
x = 2 +1 = 3 ans x = 2-1 = 1
X = 3, 1
C)
1^2 - 4(1) +3 = 1-4 +3 = 0 TRUE
3^2 - 4(3) +3 = 9 -12 +3 = 0 TRUE